Proposed scheduling scheme of jeepney operations in Malate area - Kang, Henry Ace M. (Animo Repository, 2011)
Jeepneys in the Malate area with trips to Makati, Paco and Pasay were found to dispatch vehicles with only experience and perceived demand as bases. The researchers hypothesize that due to the improper assessment of demand there is an oversupply of vehicles in all three routes. Furthermore, the inefficiency caused by this takes toll in the form of fuel consumption and cost, and manpower. The main objective of the study is to propose a scheduling scheme that improves the efficiency of the jeepney operation and service in the area of Malate, city of Manila. To accomplish this, the researchers evaluated the level of service (LOS), in terms of speed, headway and cycle time and its transport work efficiency in terms of its output or quantity offered and utilized service. Based on the traffic condition in the three study routes, the researchers proposed scheduling parameters that satisfies the demand at the maximum load section of each route while keeping in context the possibility of applying an occupancy load (level) that lessens the onboard passengers in most of the route length. The proposed parameters increased productivity, and yielded considerable amounts of savings in terms of fuel consumption and cost and manpower.